Menciptakan Kepercayaan Diri Remaja Melalui Pengembangan Kepribadian - Farida Nurfalah; Otto Fajarianto; Welly Wihayati; Rifka Noviani Santika (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
Education plays a very important role in the process of improving the quality of human resources. Improving the quality of education is a process that is integrated with the process of improving the quality of human resources itself. Resources that have the potential through a selection full of educational elements are expected to be able to help support schools in shaping students with character. The development of a student's personality can be achieved through several processes, including through his participation in organizations outside or inside school, but often students are faced with a lack of self-confidence when they are faced with social realities with various problems when they enter a social environment. Personality development is expected to be one of the solutions for them to get progress, by helping to contribute in various activities, besides that it can also make them as people who are balanced and have great concern for the environment.